Evaluation of three doses of zinc phosphites in the production of strawberry crops(Fragaria x ananassa) Carchi, Ecuador - Cuaical Galárraga, Emma Teresa; Jácome Lucero, Haddy Daniela; Mora Quilismal, Segundo Ramiro (Tierra Infinita, 2024)
With the aim of evaluating three doses of zinc phosphites to improve the production of the strawberry crop (Fragaria x ananassa) in the canton of Tulcán – Carchi province, a study was implemented within a randomized complete block experimental design. Five treatments were evaluated: T1 dose of 0.5 cc L-1, T2 dose of 1.0 cc L-1 With the aim of evaluating three doses of zinc phosphites with the aim of evaluating three doses of zinc phosphites (commercial dose), T3 dose of 1.5 cc L-1, T4 dose of 2.0 cc L-1 and T5 (absolute control), 4 replicates were performed, for a total of 20 experimental units. The treatments were applied in the cultivation, development, flowering and fruiting phases. With the data obtained, the normality test was performed (Shapiro Wilks), followed by the analysis of variance (ANOVA) and Tukey at 5%. For the variables that did not present normality, non-parametric tests were performed. Variables evaluated were plant height, total number of flowers, total number of fruits, healthy fruits, (Botrytis cinerea) incidence and severity, productivity, and cost/benefit analysis. Regarding the results obtained in terms of plant height, total number of flowers, total number of fruits, healthy fruits, severity and productivity, no statistical differences were found between treatments. Due to the variable incidence in the development phase, the best treatments were T1 and T2. The benefit/cost analysis shows that all treatments are profitable, the best being treatment T5, it is the most profitable with 4.48 dollars for every dollar invested